Resonance and cancellation phenomena in two-span continuous beams and its application to railway bridges. (1st November 2020) - Martínez-Rodrigo, M.D.; Andersson, A.; Pacoste, C.; Karoumi, R.
Highlights: Resonance and cancellation phenomena in two-span continuous bridges. Non?dimensional analytical formulation. Maximum acceleration assessment in railway bridges. Most aggressive train according to geometrical considerations. Application to real bridges from the Swedish railway network. Abstract: The objective of this study is to evaluate the vibratory response of two-span continuous beams subjected to moving loads and, in particular, to investigate the maximum resonance and cancellation of resonance phenomena. The main practical interest is the evaluation of the maximum acceleration response in railway bridges, which is one of the most demanding Serviceability Limit States for traffic safety according to current regulations. Two-span continuous bridges, in their simplest version (i.e. uniform identical spans), present antisymmetric and symmetric modes with closely spaced natural frequencies, leading to a more involved dynamic behaviour than that of simply-supported bridges. First, the free vibration response of a Bernoulli-Euler two-span beam after the passage of a single load at constant speed is formulated analytically, and non-dimensional speeds leading to cancellation or maximum response in free vibration are obtained for each mode. Then, these conditions are equated to resonant speeds induced by equidistant load series, and span length-to-characteristic distance ratios causing cancelled out resonances, or remarkably prominent ones, are obtained. Based on the previous derivations, a methodology for detecting which could be the most aggressive trains for a particular structure based on pure geometrical considerations is discussed. Finally, the applicability of the theoretical derivations is shown through the numerical analysis of two real bridges belonging to the Swedish railway network.